2002
DOI: 10.1046/j.1365-2664.2002.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of cactus weeds: implications of hybridization between control agent biotypes

Abstract: Summary 1.Results of recent research on Dactylopius opuntiae , a biological control agent for cactus weeds ( Opuntia spp.) in South Africa and elsewhere, challenge the maxim that genetic diversity of agents necessarily enhances the chances of success in biological weed control. 2. Two biotypes of D. opuntiae , each specific to a different Opuntia species, interbred freely, at least under insectary conditions. We therefore carried out cross-breeding experiments to determine the viability and host-preferences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…This potential advantage is negated because the F2 and subsequent generations produce progeny which revert to being host specific and at least half of the crawlers that are produced occur on plants on which they cannot develop (Hoffmann et al 2002;Hoffmann 2004).…”
Section: Biotypes Of Cochineal Insects and Hybridizationmentioning
confidence: 96%
See 1 more Smart Citation
“…This potential advantage is negated because the F2 and subsequent generations produce progeny which revert to being host specific and at least half of the crawlers that are produced occur on plants on which they cannot develop (Hoffmann et al 2002;Hoffmann 2004).…”
Section: Biotypes Of Cochineal Insects and Hybridizationmentioning
confidence: 96%
“…In using the two biotypes, consideration needs to be given as to what might happen when the host plants occur sympatrically and the insects are free to interbreed. Laboratory studies showed that the two biotypes interbreed freely and produce viable progeny that develop equally well on either of their parental host plant species (Hoffmann et al 2002).…”
Section: Biotypes Of Cochineal Insects and Hybridizationmentioning
confidence: 99%
“…Further tests on those species could assess the effects of hybridization, thereby avoiding possible negative outcomes as observed by Hoffmann et al. () for D. opuntiae . However, we are not aware of any cases where specificity of hybrids between two agent biotypes, both specific to the same host, would change upon hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…For example, two biotypes of Dactylopius opuntiae (Cockerell) were found to be specific to two different invasive Opuntia species (Hoffmann et al. ). Upon hybridization, the F1 generation was able to attack either host, while both host‐specific and non‐host‐specific genotypes were produced in the F2 generation potentially reducing effectiveness of biological control in monocultures of either weed (Hoffmann et al.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, regulations have become much stricter, partly due to an increasing number of studies demonstrating that different populations of a species can differ in several biological traits but most importantly also in host specificity (Hopper et al, 1993;Hoffmann et al, 2002;Mathenge et al, 2010). Given that, it is now expected that each genetically and/or geographically distinct population of an agent be tested separately for host specificity (Barratt et al, 2010), which has led to the general practice of screening agents only from a single or very few populations to keep cost down.…”
Section: Collection In the Native Rangementioning
confidence: 99%